Sodium functionalized graphene oxide coated titanium plates for improved corrosion resistance and cell viability - Marimuthu, Mohana; Veerapandian, Murugan; Ramasundaram, Subramaniyan; Hong, Seok Won; Sudhagar, P.; Nagarajan, Srinivasan; Raman, V.; Ito, Eisuke; Kim, Sanghyo; Yun, Kyusik; Kang, Yong Soo (ELSEVIER, 2014)
Surface functionalization is an important process that has been adopted to well explore the applications of nanomaterials. In this context, we demonstrate the sodium functionalized graphene oxide (NaGO) as an excellent candidate for increasing the life time of titanium (Ti) based ortho-implants. As-prepared aqueous dispersion of NaGO was used to assemble NaGO sheets on commercially pure Ti (CpTi) plates by heat controlled spin coating. The resulting wrinkled NaGO sheets play a dual role in implant material, i.e., passive layer against corrosion and biocompatible scaffold for cell viability. The preparation, physicochemical properties, and biocompatibility of NaGO coatings formed on CpTi were reported. The electrochemical polarization studies demonstrate the relative susceptibility of control GO and NaGO coatings to corrosion, which outline that the NaGO coating act as a geometric blocking layer and hence prevent the implant surface from contacting corrosive media. The immunofluorescence and cell proliferation studies performed using human dermal fibroblasts cells showed that NaGO coatings significantly (P < 0.05) enhanced the cellular viability for longer in vitro culture period (15 days) than control GO and pristine CpTi. (C) 2013 Elsevier B.V. All rights